Joseph Barcroft and the Anglo-American expedition to the Peruvian Andes (1921-1922) - Pamo, Oscar G. (2005)
Joseph Barcroft (1872-1947), British Cambridge physiologist, came to Peru at the end of 1921 leading the Anglo-American expedition in order to study the physiological characteristics that let human beings acclimatize to live at high altitude environments. They arrived to Cerro de Pasco, carrying out several measurements at different altitudes, among themselves, the Mining Co.’s American personnel and some native dwellers. This survey published as a paper two years later would arouse in 1927 Dr. Carlos Monge-Medrano (1884- 1970) and other local investigators the interest in searching for the biology and pathology of the Andean people.